Maintenance management of high rise buildings in Malaysia: A preliminary study in Klang Valley - Ibrahim, Md. Najib; Yahya, Mohamad Ridzuan (2009)
Large highrise building is relatively complicated in maintenance. This paper presents the preliminary finding of a study on the building maintenance management of selected large highrise buildings in Klang Valley, Malaysia. Four highrise buildings with a floor number ranging from 20 to 88 floors and a total floor area from 585,527 to 4,252,000 square feet were investigated. Information on maintenance policy including the type of maintenance conducted, the existence policy and budget is collected through unstructured interviews. The paper concludes that a clear maintenance policy does not exist yet in the maintenance of highrise buildings.